Konsumsi, Kecernaan Nutrien, Perubahan Berat Badan dan Status Fisiologis Kambing Bligon Jantan dengan Pembatasan Pakan - Bambang Suwignyo; Ulil Amri Wijaya; Rieska Indriani; Asih Kurniawati; Irkham Widiyono; Sarmin Sarmin (Jurnal Sain Veteriner, 2016)
This study were aimed to determine the dry matter and organic matter intake, nutrients digestibility, body weight gain and physiological status of male Bligon goats treated with feed restriction. Six Bligon goats average age of 12 months and an average body weight of 23.6 kg were fed 40% of peanut raughages (rendeng) and 60% concentrate. Goats were divided into two (2) treatment groups. Control goat treatment were fed diets based on dry matter (DM) requirements 3.5% of body weight, and feed restriction goat treatment were fed diets with 50% reduction of DM requirement. Feed restriction was conducted for 35 days. The variables measured were dry matter (DM) and organic matter (OM) intake, total digestibility nutrient (TDN) intake, body weigh gain, dry matter (DM) and organic matter (OM) digestibility, rectal temperature, respiration frequency, and heart rate. Data were analyzed by independent samples T-test. The results showed that the feed restriction significantly decreasedconsumption of DM (676.07 ± 14.76 into 372.30 ± 53.08) and OM (639.38 ± 15.89 into 349.88 ± 49.35), consumption of TDN (461.60 ± 10.23 into 253.99 ± 36.17), DM digestibility (74.39 ± 1.60 into 71.27 ± 0.89) and OM digestibility (79.42 ± 1.54 into 76.34 ± 0.24), but had no significant effect on body  temperature, respiration frequency and heart rate (pulsus) of male Bligon goat. Value of ADG was 55.24 g/day (P0) then increased to 131.43 g/day when the feed was filled back. A feed restriction up to 50% decreased goat production performance, but did not interfere with the health status of livestock (can be indicated from physiological status of goat still in the normal range).